The kinetics and mechanism of nanoconfined molten salt reactions: trimerization of potassium and rubidium dicyanamide. Issue 15 (21st April 2015) - Yancey, Benjamin; Vyazovkin, Sergey
<x xml:space="preserve">Abstract</x> Nanoconfinement accelerates the liquid state trimerization of potassium and rubidium dicyanamide but decelerates the solid state trimerization of sodium dicyanamide.